2020
DOI: 10.3390/sym12091569
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers’ Development of Meta-Cognitive Functions in Solving Mathematical-Based Programming Problems with Scratch

Abstract: Transformations, including symmetry and rotations, are important in solving mathematical problems. Meta-cognitive functions are considered critical in solving mathematical problems. In the current study, we examined prospective teachers’ use of meta-cognitive functions while solving mathematical-based programming problems in the Scratch environment. The study was conducted among 18 prospective teachers, who engaged in a sequence of mathematical problems that utilize Scratch. The data sources included video rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Moreover, the research results indicated that the PTs utilized mathematical thinking and knowledge in the encoding, representation, and decomposition meta-cognitive processes, while they utilized programming thinking with Scratch in the monitoring and evaluating processes. Scratch assistance for advancing the previous specific meta-cognitive processes is due to the visual, dynamic, and friendly interaction properties it provides [11,53]. In the planning and choosing strategy meta-cognitive processes, the research results indicated a combined utilization of mathematical, programming, and algorithmic thinking.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the research results indicated that the PTs utilized mathematical thinking and knowledge in the encoding, representation, and decomposition meta-cognitive processes, while they utilized programming thinking with Scratch in the monitoring and evaluating processes. Scratch assistance for advancing the previous specific meta-cognitive processes is due to the visual, dynamic, and friendly interaction properties it provides [11,53]. In the planning and choosing strategy meta-cognitive processes, the research results indicated a combined utilization of mathematical, programming, and algorithmic thinking.…”
Section: Discussionmentioning
confidence: 97%
“…This situation of reference was essential as the problem had to include both references in order to suit the mathematics classroom and the programming environment of the problems. Shahbari et al [35] found that the participating mathematics prospective teachers developed their meta-cognitive functions as problem solvers in both mathematics and programming aspects. Here, the prospective teachers made successful addressing of the situation of reference that considered both contents, the mathematical and the programming ones.…”
Section: Design According To the Type Of Situationmentioning
confidence: 99%
“…Researchers have been interested in metacognitive processes since Flavell [ 1 ], but generally they have been interested in the processes of students (e.g., [ 2 , 3 , 4 ]). Studies have addressed the influence of metacognition on the cognitive aspect of students’ learning (e.g., [ 5 ]), the social aspect of students’ learning (e.g., [ 6 ]), the behavioral aspect of students’ learning [ 7 ], and the affective aspect of students’ learning (e.g., [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%